Societal Rationality Bounded or Embedded? - DeMoor, Michael J. (2019)
This paper offers a characterization and critique of the idea of bounded rationality and its consequences for public policy. It offers an alternative way of accounting for the crucial features of human rationality that bounded rationality sees, using categories inspired by the Reformational philosophy of Herman Dooyeweerd and others, and then shows how this alternative account of the "bounds" of human rationality points toward an alternative orientation toward public policy-making.
Keywords: Bounded rationality; Deliberative Democracy; Pluralism; Public Policy; Rationality